2005
DOI: 10.1021/jf0477999
|View full text |Cite
|
Sign up to set email alerts
|

Residues and Half-Life Times of Pyrethrins on Peaches after Field Treatments

Abstract: The behavior of pyrethrins and piperonyl butoxide (PB) on peaches has been studied after field treatment. Three experiments were carried out at 1, 5, and 10x the concentration recommended by the manufacturer. In all experiments, the initial deposition was below the maximum residue level (MRL), and the half-life time calculated in the 10x experiment for total pyrethrins within 2.3 days was in agreement with the preharvest interval (PHI) recommended. In a model system, the photodegradation rates of the pyrethrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…The insecticidal properties of the chrysanthemum flowers were first reported in the early 1800s; the active ingredient consists of six esters called pyrethrins and identified as pyrethrin I and II, cinerin I and II, and jasmolin I and II, which are obtained from the combination of chrisanthemic acid and pyrethric acid with three alcohols: cinerolone, pyrethrolone and jasmolone (Angioni, Dedola, Minelli, Barra, Cabras, & Caboni, 2005). The relative amount of each compound vary depending on the plant type and the region where the plants are grown.…”
Section: Chemical and Biological Comparisons On Supercritical Extractmentioning
confidence: 99%
“…The insecticidal properties of the chrysanthemum flowers were first reported in the early 1800s; the active ingredient consists of six esters called pyrethrins and identified as pyrethrin I and II, cinerin I and II, and jasmolin I and II, which are obtained from the combination of chrisanthemic acid and pyrethric acid with three alcohols: cinerolone, pyrethrolone and jasmolone (Angioni, Dedola, Minelli, Barra, Cabras, & Caboni, 2005). The relative amount of each compound vary depending on the plant type and the region where the plants are grown.…”
Section: Chemical and Biological Comparisons On Supercritical Extractmentioning
confidence: 99%
“…The lack of individual effects of B. bassiana or pyrethrin applications on larval populations or other studied parameters could be due to mode of action and presumably with these biopesticides inability to reduce the daily fecundity of wheat midge adults. Furthermore, abiotic factors (e.g., sunlight, temperature) may have contributed to their lack of effect, since the previous studies have shown that fungus or pyrethrin half-life can decline rapidly (2 h to 3 d) in outdoor environments (Inglis et al, 1995;Angioni et al, 2005;Jaronski, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Pyrethrum is a mixture of six esters, pyrethrins I and II, (the most abundant), cinerin I and II, and jasmoline I and II. Sunlight photodegradation is the main factor influencing the rate of it disappearance after the application at ten times the dose recommended by the manufacturer disappearance time was 2.3 days (Angioni et al, 2005). Pyrethrum was the only botanical included in the Annex I after the fourth stage of re-evaluation.…”
Section: Pyrethrins and Azadirachtin Actual Statusmentioning
confidence: 99%